2021
DOI: 10.3390/ijms22105204
|View full text |Cite
|
Sign up to set email alerts
|

Daily Lifestyle and Inflammatory Skin Diseases

Abstract: Throughout life, it is necessary to adapt to the Earth’s environment in order to survive. A typical example of this is that the daily Earth cycle is different from the circadian rhythm in human beings; however, the ability to adapt to the Earth cycle has contributed to the development of human evolution. In addition, humans can consume and digest Earth-derived foods and use luxury materials for nutrition and enrichment of their lives, as an adaptation to the Earth’s environment. Recent studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 136 publications
0
21
0
3
Order By: Relevance
“…In addition, various chemicals are contained in tobacco, and tobacco-smoke exposure causes various harmful effects on human health. Consistently, smoking influences various inflammatory skin diseases [5] and affects the development of alopecia.…”
Section: Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various chemicals are contained in tobacco, and tobacco-smoke exposure causes various harmful effects on human health. Consistently, smoking influences various inflammatory skin diseases [5] and affects the development of alopecia.…”
Section: Smokingmentioning
confidence: 99%
“…Because of this characteristic, the skin plays various vital roles, such as protection against external stimuli and the exertion of inflammatory cytokines [3,4]. Recent studies have identified that daily lifestyle factors, such as smoking, alcohol intake, and sleep, play a vital role in the development of inflammatory skin diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…The skin is exposed to various influences from environmental alterations and stimuli, such as temperature, chemicals, microorganisms, and medications [1][2][3][4][5][6][7][8][9][10]. Indeed, representative inflammatory skin diseases such as psoriasis and atopic dermatitis are significantly influenced by various environmental factors [11][12][13][14][15]. Because of its characteristics as an outer organ, the skin is developed to tolerate, and is specialized to adapt to, these environmental changes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among various nutrient factors, fatty acids are a component of the cell membrane and contribute to signal network transduction in the body. Although there are many types of fatty acids with various physiological and pathological actions [7][8][9][10], omega-3 fatty acids, found in fish oil and nuts, have beneficial effects against human diseases and inflammatory responses [11]. In addition to their therapeutic potency [12][13][14], omega-3 fatty acids may also play a role in the development of cutaneous malignancies due to their anti-inflammatory actions [15].…”
Section: Introductionmentioning
confidence: 99%